New ECMC members: Early Career Forum. Issue 1 (March 2017) - Bos, Lieuwe D.; Langer, Daniel; Flood, Emma
I would like to introduce myself as the new chair of the Early Career Member Committee (ECMC). My name is Lieuwe Bos and I'm situated in Amsterdam, the Netherlands, where I also defended my PhD thesis under supervision of Prof. Peter Sterk (respiratory medicine) and Prof. Marcus Schultz (intensive care). I continued my clinical training in pulmonology in Amsterdam in the group of Prof. Elisabeth Bel. A message from the new chair of the @ERStalk ECMC http://ow.ly/QmaL307Ykcx